Ferromagnetism in graphene oxide. (2021) - Sinha, Apurva; Ali, Anzar; Thakur, Ajay D.
Abstract: Presence of d and/or f electrons is considered essential for the origin of localized magnetic moments in material systems. In addition to this, the presence of an exchange interaction between these localized moments is crucial for the observation of an ordered magnetic ground state (including ferromagnetism). The existence of a ferromagnetic ground state in such system is therefore not a very exciting pursuit. Despite this, ferromagnetism was reported in carbon-based materials in past which was attributed to the presence of vacancies, structural defects, edge-states and adatoms. At a fundamental level, it is impossible to generate localized magnetic moments in carbon based systems that contain exclusively of pure sp 3 carbons / sp 2 carbons / sp carbons. But, the existence of such moments can be favored in systems having a mixed hybridization like sp 2 – sp 3 character as then some of the electrons remain deprived of bonding and could be the source of local moments. Graphene oxide (GO) is comprised of sp 2 bonded graphene like sheet with attached functional groups that contain sp 3 carbon atoms, thus having mixed hybridization. Therefore, GO and its derivatives are interesting systems to study carbon based magnetic ordering. We report the observation of weak ferromagnetic behavior in GO samples prepared using a modified Hummer's method. The M−H hysteresis loop shows the maximum moment of 0.002 emu/g. The existence of localized magnetic moments is explained using the presence of carbon networks/chains with mixed sp 2 – sp 3 character. We also discuss the reasons for the origin of exchange interaction in these systems.